Exploring Rural-based Secondary School Teachers’ Professional Development Needs in Teaching English Pronunciation in Vhembe District, South Africa - Ndishunwani Vincent Demana; Ernest Kwesi Klu; Mzamani Johannes Maluleke (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2026)
This study explores the professional development needs of rural secondary school teachers in teaching English pronunciation in the Vhembe District of South Africa. Recognizing that pronunciation is a critical yet often neglected component of English language instruction, the study investigates how teachers perceive, approach, and manage pronunciation teaching in resource-limited rural contexts. A qualitative research design was adopted, involving semi-structured interviews with English teachers from selected rural secondary schools. The findings reveal that most teachers have limited formal training in pronunciation pedagogy and rely on intuitive or traditional methods of instruction. Challenges such as inadequate teaching resources, linguistic interference from indigenous languages, and the marginalization of pronunciation in the curriculum further hinder effective instruction. Despite these challenges, teachers demonstrated a strong willingness to improve their practice and called for targeted professional development, accessible teaching materials, and sustained institutional support. The study recommends integrating explicit pronunciation pedagogy into teacher education programmes, providing regular in-service training, and revising the curriculum to give pronunciation a more prominent role. These interventions are essential to empower rural teachers, enhance learners’ spoken English proficiency, and promote equity in language education across South Africa.